IMPROVING STUDENTS' MOTIVATION AND LEARNING OUTCOMES IN SIRAH LEARNING THROUGH SCIENTIFIC APPROACHES AND COMIC MEDIA - Rima Nurkomala; Jubaidah Jubaidah; Asep Sopian (Universitas Muhammadiyah Tapanuli Selatan, 2023)
In Sirah learning, low motivation and student learning outcomes motivate classroom action research (CAR). Using a scientific approach and comic books, this CAR aims to increase student motivation and learning outcomes in Sirah learning. CAR was performed in two cycles because an average value of more than 85 was obtained with a Minimum Value of 80 in the second cycle. Planning, implementing, observing, and reflecting were all part of each cycle. Students from Ali bin Abi Talib SMPIT As Syifa Boarding School Jalancagak took part in the study. Student activity observation sheets, an assessment matrix rubric, and a student response questionnaire to learning were the instruments used to collect data.Based on the findings and discussions, it was concluded that there was an increase in the learning motivation of Ali Bin Abi Talib SMPIT As Syifa Boarding School class VIII students in the Sirah subject increased from 64.9 (sufficient) in cycle 1 to 85.16 (very good) in cycle 2, as did student learning outcomes, particularly in the domain of cognitive, which increased from 40.18 (poor) in cycle 1 to 87.09 (very good) in cycle 2. The part of knowledge improved from 81.5 (good) to 89. (very good)